QIROAH DAN KEARIFAN LOKAL: UPAYA MEMBANGUN PEMBELAJARAN KONTEKSTUAL DI SMA MUHAMMADIYAH 2 PALEMBANG - Nurhalizah; Imron, Kristina; Sabana, Rendi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning qirā’ah in senior high schools still faces various challenges, particularly the low relevance of reading materials to students’ real-life contexts. This condition results in suboptimal reading comprehension and low learning motivation among students. This study aims to develop a qirā’ah learning model based on local wisdom as an effort to create contextual learning. The research employs a Research and Development (R&D) approach, consisting of needs analysis, design, development, validation, revision, and product testing stages. Data collection techniques include observation, questionnaires, interviews, and tests. The results indicate that the locally based qirā’ah teaching materials developed are considered valid by material and media experts and are practical for classroom use. Furthermore, the trial results show an improvement in students’ reading abilities after using the developed materials. Therefore, the development of qirā’ah materials based on local wisdom is effective in realizing contextual and meaningful Arabic language learning for students.